THE ROLE AND IMPORTANCE OF METEOROLOGY IN MODERN ARMED CONFLICTS (Modern American Journal of Engineering, Technology, and Innovation, 2025)
This article analyzes the importance of meteorology in modern armed conflicts, its impact on military strategy and tactics, including the effectiveness of weapons, and its role in choosing the time and location of hostilities. The article also discusses the presentation of meteorological data in real time and their importance for military intelligence using satellite technology.